2013
DOI: 10.1111/dewb.12034
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Conundrums: The Ethics of Epidemiology and the Problems of Population in Implementing Pre‐Exposure Prophylaxis

Abstract: The impending implementation of pre-exposure prophylaxis (PrEP) has prompted complicated bioethical and public health ethics concerns regarding the moral distribution of antiretroviral medications (ARVs) to ostensibly healthy populations as a form of HIV prevention when millions of HIV-positive people still lack access to ARVs globally. This manuscript argues that these questions are, in part, concerns over the ethics of epidemiological science and knowledge production practices. Questions of distribution, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although drug resistance was rare in the IPrEx study [ 47 ], concerns remain over the use of front-line antiviral drugs as microbicides because of the potential for development of viral resistance. In addition, there are ethical concerns regarding the circulation of antiretroviral drugs (ARVs) to healthy individuals when many HIV-positive individuals lack access to primary treatment with ARVs [ 48 ]. The novel vaginal formulation described in this paper, has the potential to provide women with a non-antiretroviral approach to prevent HIV-1 infection by enhancing the protective properties of the vaginal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Although drug resistance was rare in the IPrEx study [ 47 ], concerns remain over the use of front-line antiviral drugs as microbicides because of the potential for development of viral resistance. In addition, there are ethical concerns regarding the circulation of antiretroviral drugs (ARVs) to healthy individuals when many HIV-positive individuals lack access to primary treatment with ARVs [ 48 ]. The novel vaginal formulation described in this paper, has the potential to provide women with a non-antiretroviral approach to prevent HIV-1 infection by enhancing the protective properties of the vaginal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Disjuncture exists between political mandates and legislative oversight (Oswin, 2007;L. Rispel, 2009;Sember, 2009), societal and community attitudes of same sex behavior among men (Smith, Tapsoba, Peshu, Sanders, & Jaffe, 2009), the social stigma and discrimination associated with hiv transmission through same sex behavior among men (Cloete, Simbayi, Kalichman, Strebel, & Henda, 2008), and cultural beliefs about masculinity (Fiereck, 2015b;Isaacs & McKendrick, 1992;Y. M. Sikweyiya, Jewkes, & Dunkle, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study found stigma related to promiscuity and medical mistrust to be associated with lack of interest in PrEP [ 21 ]. However, this analysis did not specifically address the unique perspectives and barriers faced by the transgender community since it combined data for MSM and TGW [ 22 ]. Qualitative data from San Francisco, CA suggest that integration of the unique needs and characteristics of the transgender community into PrEP promotion strategies is essential to improving PrEP uptake in this population [ 15 ].…”
Section: Introductionmentioning
confidence: 99%